Product Standards and Firms’ Export Decisions - Fernandes, Ana M.; Ferro, Esteban; Wilson, John S. (World Bank, Washington, DC, 2015)
The paper estimates the effect of product standards on firms’ export decisions using two novel datasets. The first covers all exporting firms in 42 developing countries. The second covers pesticide standards for 243 agricultural and food products in 63 importing countries over 2006–12. The analysis shows that product standards significantly affect foreign market access. More restrictive standards in the importing country, relative to the exporting country, lower firms’ probability of exporting as well as their export values and quantities. The relative restrictiveness of standards also deters exporting firms from entering new markets and leads to higher exit rates from those markets. Moreover, firm characteristics mediate the effect of product standards on firms’ export decisions. Smaller exporters are more negatively affected in their market entry and exit decisions by the relative stringency of standards than larger exporters. Positive network effects of exporters from the same country may help reduce the burden of importing countries’ standards on firms’ decisions to enter new markets.